Projeto e implementação de um sistema de autoria para animações, simulações e treinamentos em realidade virtual - BARATA, Pebertli Nils Alho (Universidade Federal do Pará, 2012)
This dissertation presents the design, development and implementation of a software for the creation of animation, simulations and training processes and industrial technical instructions, also presents the architecture used for its implementation. The software presented allows the generation of animation, texts, sounds and interactions, providing tools for creating, display and supervision of simulation with use of Virtual Reality 3D. The dissertation also deals with the practical use of the software through a case study with simulations 3D in real industrial processes of a plant for generation of electric energy. This study also contributes to the areas of training and virtual reality and systems of authorship 3D to submit innovative concepts in the area of supervision automatic, also showing a possible structure of software components for use in the areas mentioned. May also be highlighted the review of similar technologies to the purpose of this study, aiming to the identification of influences, improvements and innovations in the areas of authorship 3D and training.